Developing an Image Caption Generator with Big Data and Machine Learning Techniques (International Journal of Food and Nutritional Sciences, 2023)
The Image Caption Generator is asophisticated process that involves recognizing thecontextual details of an image and annotating it withrelevant captions, employing deep learning andcomputer vision technologies.